Classical Philology in the Grip of Ideology (1940–1953) - Juchnevičienė, Nijolė (Literatūra, 2013)
Before the first Vilnius occupation in 1939 by the Red Army, in the territory of the nowadays’ Lithuania there were two centres of Classical Philology: at Kaunas University (established in 1922) and Vilnius University (re-establihed by the Lithuanian government in 1918, after 86 years from its closure by the Russian Tsar Nikolas I because of the students’ participation in the upraisal of 1832). From 1919, Vilnius was incorporated in to Poland, and the university was named after the king Stefan Batory. After the annexation of Lithuania by the USSR in 1940 and again in 1944, the majority of intelligentsia were either exiled to Siberia or fled from the country to the West (among them – the absolute majority of professors, staff and students of Vilnius University). The scanty intelligentsia that stayed in Lithuania had to revitalize the classical studies under the severe circumstances of the post-war period and experienced a hard spiritual and physical terror. Highly qualified specialists had to bear the degrading “examination of loyalty”, were persecuted and checked in different ways, and forced to “re-educate themselves”. After 1944, all classical courses were concentrated at the Vilnius University . The University reopened in 1944, but its structure and curriculum were totally changed. The University was made Soviet and subdued to a strict party control. Humanities and social sciences suffered most as those most pertinent to ideology. The apparatus of the LCP(B) CC controlled and regulated all areas of culture and education. The principal goal of the Communist Party was to control the cultural and spiritual life of society. The intellectuals were forced not only to follow the communist ideology, but also to demonstrate the advantages of the Soviet system and the exclusiveness of the Russian nation. With sensitive reactions to what happened in Moscow, campaigns of a harsh treatment of scientists and scholars of different fields were initiated. Ideological activity was regarded to be essential in one’s academic carrier. The minutes of the Department of Classical Philology, kept at the Vilnius University Archives, bear witness to the University life at that time and give the best insight into the mental ways that helped the Department and classical philology in Lithuania to survive. The preserved texts are pieces of rhetoric, a peculiar sort of Soviet second sophism. Nobody, including the speaker, was supposed to believe in what was said. The conformism illustrated above was not a goal in itself and did not reveal the true state of mind. The majority of Lithuanian intellectuals managed to combine conformism with the so-called “conservationism” which expressed itself in the use of one’s position to do whatever was deemed possible for the benefit of the nation. The Department remained to be the most important cultural factor in its efforts to preserve the European dimension of the Lithuanian culture.